(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Gastric ulcers, also known as stomach ulcers, are open sores that form on the stomach's lining. Additionally, a section of the intestine right above the stomach may develop ulcers. Purpose: The purpose of our study was to examine the morphological changes in GMS in chronic gastritis patients who smoke (lay) tobacco "NAS" and reside in unfavorable environmental conditions in the South Aral Sea region. Materials and methods: A total of 100 patients having stomach ulcers were selected for the study and were divided randomly into 4 different Group A: control group (n=40) consists of patients having ulcers but no habit of NAS. Group B, C and D consists of patients having ulcers as well as the habit of smoking NAS for 1-5 years (n=12), 6-10 years (n=36) and more than 11 years (n=12) respectively. The biopsy samples were taken using the esaphago-gastroduodenofibroscopy technique. The staining was done using haematoxylin–eosin according to the manufacturer’s protocol and was morphologically analyzed using morphological classification. Results: The results showed that in the control group, atrophic gastritis without and with epithelial remodelling was (12.5% and 5% respectively) observations, atrophic-hyperplastic gastritis was 22.5%, while the maximum was in group C n=36; there were 8.1% cases of superficial gastritis and 28% cases of hypertrophic gastritis. Conclusion: It can be concluded that long-term use of tobacco ‘NAS’ is responsible for chronic gastritis and there should awareness programs be conducted to aware people adverse effects of tobacco on human body parts as well as there should be focus on medicines to treat the illness.